In vivo evidence by magnetic resonance volumetry of a gestational age dependent response to tracheal occlusion for congenital diaphragmatic hernia. (29th September 2015) - Nawapun, Katika; Eastwood, Mary Patrice; Diaz‐Cobos, Daysi; Jimenez, Julio; Aertsen, Michael; Gomez, Olga; Claus, Filip; Gratacós, Eduard; Deprest, Jan
Abstract: Objective: We aimed to assess in vivo changes in lung and liver volumes in fetuses with isolated congenital diaphragmatic hernia, either expectantly managed or treated in utero. Method: This is a secondary analysis of prospectively collected data at two fetal therapy centers. We used archived magnetic resonance images of fetuses taken ≥7 days apart, creating paired observations in 20 expectantly managed cases, 41 with a second magnetic resonance prior to balloon reversal and 64 after balloon removal. We measured observed to expected total fetal lung volume (O/E TFLV) and liver‐to‐thoracic volume ratio. We calculated changes in volume as compared with the initial measurement and its rate as a function of gestational age (GA) at occlusion. Results: The liver‐to‐thoracic volume ratio did not change in either group. In expectantly managed fetuses, O/E TFLV did not increase with gestation. In fetuses undergoing tracheal occlusion, the measured increase in volume was 2.6 times larger with balloon in place as compared with that after its removal. GA at tracheal occlusion was an independent predictor of the O/E TFLV. The net rate seems to initially increase and plateau at a maximum of 1.5% per week by 35 to 45 days after occlusion. Conclusions: Tracheal occlusion induces a net increase in volume, its magnitude essentially dependent on the GA at occlusion. © 2015 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? In expectantly managed congenital diaphragmatic hernia fetuses, lung hypoplasia may be progressive with wide interindividual variability. Lung volume increases after tracheal occlusion. What does this study add? Tracheal occlusion induces a net increase in fetal lung expansion rate up to 1.5% per week, its magnitude essentially dependent on the gestational age at occlusion.